The recruitment process - Collins, D.; MacNamara, A. (Talent development: A practitioner guide, 2018)
Given that many sports still recruit from as young as seven years of age, the need for parents and coaches to understand the pitfalls and realities of talent identification is obvious. This chapter provides a critical commentary of the talent identification (TI) processes in sport and key considerations for coaches and parents. The limitations of using performance and anthropometric factors as criteria for selection, especially at pre-pubescent stages of development, are discussed and the impact of the relative age effect as a significant influencer on talent identification and development is debated. The practical impact of selection and TI policies that positively discriminate in favour of early maturing individuals who perform best at the time of testing (rather than identifying their potential to develop in the future) is explored from the perspective of both those who `make it` into system and those who fail to be selected.